FLEBOTOMÍNEOS (diptera: Psychodidae) no Peridomicílio De moradores da Zona Rural do Município de Iúna, Espírito Santo - Faria, Humberto Gripp de (2017)
Considering the importance of sandfliesin the transmission cycles of leishmaniasis, this study aimed to evaluate the local fauna of the species vectors of the disease in an area of endemic transmissionto American Cutaneous Leishmaniasis (ACL). Samples were collected in the rural regions of the municipality of Iúna, state of Espírito Santo, Brazil. Diptera catches were made infive rural locations where cases ofACLhad previously been reported. Fourteen collection points were established in the peridomicile of residents of these localities. The selection criteria for the installation of the traps were properties with a previous history of human clinical cases of tegumentary leishmaniasis and currently with dogs without clinical signs of the disease, and may be seropositiveor not for antigens of Leishmania (Viannia) braziliensisby the technique of conventional indirect ELISA (Enzyme-Linked Immunosorbent Assay), and that they had been vaccinated against Visceral Canine Leishmaniasis with commercial vaccines.The catches were carried out in December of 2015 respecting the behavioral habits of the insects. The collections were carried out with the aid of "CDC" light traps (Centers for Diseases Controls) installed at 6:00 p.m. and collected at 06:00 a.m., totaling 336 operating hours. Between thefourteen collection points, ten presented the presence of sand flies, with a total of 1148 specimens.A sample of 60 females, 20 of each of the three points with higher frequencies of sandflies, were separated and submitted to DNA extraction and then the polymerase chain reaction(PCR),with the intentionto verify the presence of nucleic acids compatible with the genus Leishmaniaspp. in their digestive tubes, however, all analyzes showed negative results.The remaining 1088 phlebotomineswere processed and subsequently identified. Migonemyia migonei was the most abundant species in this study, accounting for 71.7% of the specimens, followed by Nyssomyia intermedia 21.5%, the other species added 6.8%. Considering the vector capacity of Mg. Migoneiand Ny. Intermedia, as well as their anthropophilic habits already described in the literature, we can suggest that these species may be acting as transmitters of ACL in the region.